Salvelinus_Genotypes - Savary, Romain; Dufresnes, Christophe; Champigneulle, Alexis; Caudron, Arnaud; Dubey, Sylvain; Perrin, Nicolas; Fumagalli, Luca (Dryad Digital Repository, 2017)
Genotypes (N=378) of Salvelinus alpinus for 8 microsatellite loci